1994
DOI: 10.1200/jco.1994.12.12.2614
|View full text |Cite
|
Sign up to set email alerts
|

Osteosarcoma recurrences in pediatric patients previously treated with intensive chemotherapy.

Abstract: The most important prognostic indicator at first recurrence seems to be the possible complete resection of disease. Patients not amenable to surgery and patients with a second or a third recurrence have a poor prognosis. The potential benefit of more aggressive treatments such as high-dose chemotherapy and autologous bone marrow transplantation should be investigated for these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
110
1
1

Year Published

1997
1997
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 129 publications
(123 citation statements)
references
References 23 publications
11
110
1
1
Order By: Relevance
“…In many series, the number of patients treated with second-line chemotherapy was too small to draw conclusions regarding the impact on survival. 7,21 Pastorino et al 13 and Tabone et al 15 observed no difference in survival with or without second-line chemotherapy. However, chemotherapy was given selectively to patients with multiple pulmonary nodules or with an RFI shorter than 1 year RFI 13 or to patients with multiple recurrent tumors or tumors that were difficult to resect.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…In many series, the number of patients treated with second-line chemotherapy was too small to draw conclusions regarding the impact on survival. 7,21 Pastorino et al 13 and Tabone et al 15 observed no difference in survival with or without second-line chemotherapy. However, chemotherapy was given selectively to patients with multiple pulmonary nodules or with an RFI shorter than 1 year RFI 13 or to patients with multiple recurrent tumors or tumors that were difficult to resect.…”
Section: Discussionmentioning
confidence: 96%
“…However, chemotherapy was given selectively to patients with multiple pulmonary nodules or with an RFI shorter than 1 year RFI 13 or to patients with multiple recurrent tumors or tumors that were difficult to resect. 15 In contrast, Saeter et al 19 concluded that the delivery of "modern intensive chemotherapy" (p. 1090) improved overall survival when compared with patients treated with no or inadequate chemotherapy. In two more recent series, a benefit for second-line chemotherapy was not demonstrated.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations